Research on Disaster-Control Method of Metro Station in Soft Fluid-Plastic Stratum - Wang Hongbo; Qingsong Zhang; Liu Rentai; Peng Jiang; Yankai Liu (Advances in Civil Engineering)
Soft and broken ground is a common geological condition for subway pit water damage. The complex hydrogeological environment is the main cause of frequent disasters. It relied on the inrush water project of the soft fluid-plastic stratum in the pit of the Shang Yuanmen station in Nanjing. And based on the geological data and the actual site of the project, the station was evaluated for hazards and analysis of major and difficult points. Combined with a variety of geophysical exploration methods, the source of water in the foundation pit and the key areas for pulp reinforcement was obtained. Based on field tests and indoor tests of grouting reinforcement, the parameters before and after grouting reinforcement were analyzed. The effect of material proportioning and grouting pressure on the parameters of stratum reinforcement was studied. It revealed the effect of the behavioral mechanism of material properties and grouting pressure on different mechanical indexes. It creatively proposes a localized controlled grouting process and uses COMSOL modeling to explain its reinforcement mechanism. In addition, foundation pits applied a full set of monitoring system. Finally, a complete set of comprehensive control methods were formed for water inrush in soft fluid-plastic stratum of complex urban strata. Then, the methods are implemented at the project site. Practice has proved that this method successfully seals the inrush water and reinforces foundation pits while ensuring the safety of foundation pits and surrounding construction pipelines. It is hoped that this method can be used as a reference for similar projects.